The Community Earth System Model Version 2 (CESM2). (6th February 2020) - Danabasoglu, G.; Lamarque, J.‐F.; Bacmeister, J.; Bailey, D. A.; DuVivier, A. K.; Edwards, J.; Emmons, L. K.; Fasullo, J.; Garcia, R.; Gettelman, A.; Hannay, C.; Holland, M. M.; et al.
Abstract: An overview of the Community Earth System Model Version 2 (CESM2) is provided, including a discussion of the challenges encountered during its development and how they were addressed. In addition, an evaluation of a pair of CESM2 long preindustrial control and historical ensemble simulations is presented. These simulations were performed using the nominal 1° horizontal resolution configuration of the coupled model with both the "low‐top" (40 km, with limited chemistry) and "high‐top" (130 km, with comprehensive chemistry) versions of the atmospheric component. CESM2 contains many substantial science and infrastructure improvements and new capabilities since its previous major release, CESM1, resulting in improved historical simulations in comparison to CESM1 and available observations. These include major reductions in low‐latitude precipitation and shortwave cloud forcing biases; better representation of the Madden‐Julian Oscillation; better El Niño‐Southern Oscillation‐related teleconnections; and a global land carbon accumulation trend that agrees well with observationally based estimates. Most tropospheric and surface features of the low‐ and high‐top simulations are very similar to each other, so these improvements are present in both configurations. CESM2 has an equilibrium climate sensitivity of 5.1–5.3 °C, larger than in CESM1, primarily due to a combination of relatively small changes to cloud microphysics and boundary layer parameters. In contrast, CESM2's transient climate response of 1.9–2.0 °C is comparable to that of CESM1. The model outputs from these and many other simulations are available to the research community, and they represent CESM2's contributions to the Coupled Model Intercomparison Project Phase 6. Plain Language Summary: The Community Earth System Model (CESM) is an open‐source, comprehensive model used in simulations of the Earth's past, present, and future climates. The newest version, CESM2, has many new technical and scientific capabilities ranging from a more realistic representation of Greenland's evolving ice sheet, to the ability to model in detail how crops interact with the larger Earth system, to improved representation of clouds and rain, and to the addition of wind‐driven waves on the model's ocean surface. The data sets from a large set of simulations that include integrations for the preindustrial conditions (1850s) and for the 1850‐2014 historical period are available to the community, representing CESM2's contributions to the Coupled Model Intercomparison Project Phase 6 (CMIP6). Key Points: Community Earth System Model Version 2 includes many substantial science and infrastructure improvements since its previous version Preindustrial control and historical simulations were performed with low‐top and high‐top with comprehensive chemistry atmospheric models Comparisons to observations are improved relative to previous versions, including major reductions in radiation and precipitation biases